Main Directions of Increasing Competitiveness Considering Specificity of Agriculture and Its Sustainable Development - ZHUSSUPOV, Yerzhan; TURSUMBAYEVA, Madina; SHOKHAN, Roza; AIMURZINA, Baglan; KAMENOVA, Mazken; OMAROVA, Ainura (Journal of Environmental Management and Tourism; Vol 11 No 7 (2020): JEMT Volume XI Issue 7(47) Winter 2020DO - 10.14505//jemt.11.7(47).22, 2020)
Agriculture is one of the key sectors of the economy of Kazakhstan, providing food and economic security, as well as the labor potential of the country. Increasing the competitiveness of domestic agricultural products and products of its processing is closely related to the need to promote and position domestic products both in the domestic market and export markets. The analysis of the state of the Kazakh market of agricultural products at the present stage is carried out and alternative strategies are proposed to increase production efficiency based on the digitalization and sustainability of agriculture.